Semiotic Meanings of Videos of Stanford Medicine YouTube Channel - Metta Indah Jayanti; Erika Sinambela; Arsen Nahum Pasaribu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This thesis is an analysis of non-verbal semiotic symbol signs in Covid-19 videos of Stanford Medicine YouTube channel to find out the kinds of signs dominantly found in Covid-19 Videos of Stanford Medicine YouTube Channel, how the meanings of the signs are realized in Covid-19 Videos of Stanford Medicine YouTube Channel, and why those kinds of signs are dominantly found in Covid-19 Videos of Stanford Medicine YouTube Channel. To answer the problem, the researcher used the theories of semiotics proposed by C. S. Peirce supported by Danesi (2010) and Wierzbicka (1996). The kinds of sign were analysed by the triadic semiotic theory of Peirce, the meanings of signs were analysed by the non-verbal theory of Danesi, and the color meaning was analysed by color theory of Wierzbicka. The research method is descriptive qualitative approach. It is descriptive qualitative because the researcher used interpretive analysis to analyze the sign on Covid-19 videos. The researcher found that out of the three sign categories, the type of sign that appeared most often is the ground category, followed by object and interpretant. The total signs from ground category is 83 times occured in the data. There are three kinds of sign on ground namely, icon, index, and object. The total of icon occured is 49 times, the total of index occured is 4 times, and the total of object occured is 30; The total signs from object category is 47 times occured in the data. From three kinds of sign on object only two kinds occured. They are qualisign and legisign. Sinsign never occur. The total of qualisign occured is 43 times, while the total of legisign occured is 4 times; and the total signs from interpretant category is 30 times occured in the data. From three kinds of sign on interpretant, only two kinds occured. They are rheme and argument. Decisign never occur. The total of rheme occured is 15 times, while the total of argument occured is also 15 times.